Burst Suppression During General Anesthesia and Postoperative Outcomes: Mini Review - Pawar, Niti; Barreto Chang, Odmara L. (Frontiers in Systems Neuroscience, 2022)
In the last decade, burst suppression (BS) has been increasingly studied by many to examine whether it is a mechanism leading to postoperative cognitive impairment. Despite a lack of consensus across trials, the current state of research suggests that electroencephalogram (EEG) burst suppression, duration and EEG emergence trajectory may predict postoperative delirium (POD). A mini literature review regarding evidence about BS impact and susceptibilities was conducted, resulting in conflicting studies. Primarily, studies have used different algorithm values to replace visual BS examination, although many studies have since emerged showing that algorithms underestimate BS duration. As these methods may not be interchangeable with visual analysis of raw data, it is possibly a factor for the current heterogeneity between data. Even though additional research trials incorporating the use of raw EEG data are necessary, the data currently shows that intraoperative EEG monitoring may help physicians identify BS and guide anesthetic titration during surgery. These modifications could lead to preventing unfavorable outcomes. Furthermore, some studies suggest that age, baseline impairment, and certain medications are risk factors for BS and POD. These patient characteristics, in conjunction with intraoperative EEG monitoring, could be used for individualized patient care. Future studies on the feasibility of raw EEG monitoring, new technologies for anesthetic monitoring and titration, and patient-associated risk factors are crucial to our continued understanding of BS and POD.